Dominant Factors Behavioral Intention of The Generation Millennials in Using E-Wallets - Nana Triapnita Nainggolan; Darwin Lie; Lora Ekana Nainggolan; Ady Inrawan; John Lidia (UNIVERSITAS PAKUAN, 2023)
Technological advancements fueled by the internet revolution have transformed the financial services industry's image, resulting in modifications to electronic financial services. These service changes can be seen in almost all forms of financial services, such as banking, insurance, and stock trading, which are carried out using electronic media, such as E-wallets services. This study's primary goal is to discover how the Millennial generation uses digital wallet applications in terms of perceived ease of use, perceived usefulness, trust, social influence. This study utilized a quantitative method using exploratory surveys and online questionnaires, as well as a literature and field research design. This study employs the Smart PLS program with the PLS-SEM approach for data analysis. Data was collected using non-probability sampling using a purposive sampling approach, yielding a sample size of 146 respondents for this research. This research provides information about the behavior of using digital wallet applications, which are significantly controlled by perceived ease of use, trust, and social influence. Furthermore, the Perceived Usefulness factor does not significantly impact the behavior of using digital wallet applications. These findings highlight the importance of trust as a motivator for customers when utilizing an E-Wallet application. It is preferable to expand the number of study samples in order to appropriately generalize findings, as well as to include research factors that are believed to influence behavioral intention to use. This research will look at the effects of perceived ease of use, perceived utility, trust, and social influence on Generation Millennial behavior when it comes to using digital wallets.